An introduction to medical statistics - Bland, Martin (Oxford University Press, 2015)
An Introduction to Medical Statistics, fourth edition, is a 'must-have' textbook. Written in an easy-to-understand style and packed with real life examples, the text clearly explains the common statistical methods seen in published research and guidelines, as well as how to interpret and analyse statistics for clinical practice.